2017
DOI: 10.18632/oncotarget.22733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathogenic germline variants detected by multigene sequencing in unselected Japanese patients with ovarian cancer

Abstract: Pathogenic germline BRCA1, BRCA2 (BRCA1/2), and several other gene variants predispose women to primary ovarian, fallopian tube, and peritoneal carcinoma (OC), although variant frequency and relevance information is scarce in Japanese women with OC. Using targeted panel sequencing, we screened 230 unselected Japanese women with OC from our hospital-based cohort for pathogenic germline variants in 75 or 79 OC-associated genes. Pathogenic variants of 11 genes were identified in 41 (17.8%) women: 19 (8.3%; BRCA1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 33 publications
(37 reference statements)
5
51
2
Order By: Relevance
“…Alsop et al (Australia) reported a g BRCA mutation prevalence of 17.1% in patients with high-grade serous carcinoma, and Norquist et al (USA) found a combined g BRCA1 and g BRCA2 prevalence of 16.0% 8 19. Nonetheless, the results of our study are consistent with a recent study in Japan that reported a g BRCA prevalence of 29.7% in patients with high-grade serous carcinoma 4. In this study, patients with mucinous cancers did not have g BRCA mutations, which is consistent with the statement of the NCCN guidelines 12.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alsop et al (Australia) reported a g BRCA mutation prevalence of 17.1% in patients with high-grade serous carcinoma, and Norquist et al (USA) found a combined g BRCA1 and g BRCA2 prevalence of 16.0% 8 19. Nonetheless, the results of our study are consistent with a recent study in Japan that reported a g BRCA prevalence of 29.7% in patients with high-grade serous carcinoma 4. In this study, patients with mucinous cancers did not have g BRCA mutations, which is consistent with the statement of the NCCN guidelines 12.…”
Section: Discussionsupporting
confidence: 92%
“…Hirasawa et al conducted a single-center study and reported a g BRCA mutation prevalence of 11.7% 4. International studies also reported similar findings; 13.8% in a European and US multicenter study and 12.1% in a Taiwanese study 16 17.…”
Section: Discussionmentioning
confidence: 78%
“…Efforts to identify additional moderate-to-high-risk hereditary breast and ovarian cancer (HBOC) genes have largely been restricted to candidate gene approaches using targeted nextgeneration sequencing (NGS) panels of known cancer predisposition genes [12][13][14][15][16][17][18] , which have collectively only resolved a very small proportion of unexplained families. Although three studies utilised data from whole-exome sequencing (WES) of BRCA1 and BRCA2-negative ovarian carcinoma patients [19][20][21] , these analysed only a subset of candidate genes in the available data and included non-HGSOC tumour types in their case cohorts.…”
mentioning
confidence: 99%
“…Whereas for ovarian cancer, the lifetime risk in ordinary groups is 1.5%; for Lynch syndrome, it is 3-20% [30,34,35]. In a recent report in Japan, it was stated that a pathogenic variant of an MMR gene was recognized in 2.6% of epithelial ovarian cancer cases [36].…”
Section: Clinicopathological Features Of Dmmr Gynecological Cancermentioning
confidence: 99%